2021
DOI: 10.1101/2021.07.15.21260621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody and T cell responses to Sinopharm/BBIBP-CorV in naïve and previously infected individuals in Sri Lanka

Abstract: Background: As there are limited data of the immunogenicity of the Sinopharm/BBIBP-CorV in different populations, antibody responses against different SARS-CoV-2 variants of concern and T cell responses, we investigated the immunogenicity of the vaccine, in individuals in Sri Lanka. Methods: SARS-CoV-2-specific antibodies were measured in 282 individuals who were seronegative at baseline, and ACE2 receptor blocking antibodies, antibodies to the receptor binding domain (RBD) of the wild type (WT), B.1.1.7, B.1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 18 publications
5
39
4
Order By: Relevance
“…Although 19/25 individuals responded to the N protein of SARS-CoV-2, these responses were of very low frequency and were several folds lower than the responses to S1 subunit. The frequency of N protein speci c ASCs were also several fold lower than what we previously observed for the Sinopharm/BBIBP-CorV, which is an inactivated vaccine and therefore, induces immune responses to the N protein17 . Therefore, these low frequency memory T cell responses are likely to be due to pre-existing cross reactive memory B cell responses to other seasonal coronaviruses and are unlikely to…”
contrasting
confidence: 69%
See 2 more Smart Citations
“…Although 19/25 individuals responded to the N protein of SARS-CoV-2, these responses were of very low frequency and were several folds lower than the responses to S1 subunit. The frequency of N protein speci c ASCs were also several fold lower than what we previously observed for the Sinopharm/BBIBP-CorV, which is an inactivated vaccine and therefore, induces immune responses to the N protein17 . Therefore, these low frequency memory T cell responses are likely to be due to pre-existing cross reactive memory B cell responses to other seasonal coronaviruses and are unlikely to…”
contrasting
confidence: 69%
“…Of those who were baseline seronegative, 56/69 (81.2%) responded to RBD of WT, 49/69 (71.0%) to B.1.1.7, 25/69 (36.2%) to B.1.351 and 44/69 (63.8%) to B.1.617.2 (Fig.2A). The RBD HAT titres were signi cantly lower for the WT (p < 0.0001), B.1.1.7 (p < 0.0001), B.1.351 (p = 0.001), B.1.617.2 (p = 0.0003) compared to titres of convalescent sera of naturally infected individuals (n = 36)17 . The mean HAT titres for Gam-COVID-vac were similar to the WT (95.6 vs 94.1), B.1.1.7 (62.9 vs 48.8) and for B.1.617.2 (73.9 vs 70.4), compared to our previously published data following a single dose of AZD1222.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In the current context, the government of Sri Lanka commenced the national COVID-19 vaccination program following its emergency approval of Oxford-AstraZeneca/ChAdOx1 nCoV-19, Sinopharm/BBIBP-Cor V, and Sputnik-V/Gam COVID-Vac and Pfizer-BioNTech/tozinameran. In addition, Jeewandara et al, 2021 recently showed a high seroconversion rate following two doses of Sinopharm/BBIBP-Cor V in his study (6). However, an in-depth analysis of the clinical data and real-world impacts of COVID-19 vaccines, along with immunogenicity data, is essential to comprehend the real picture in Sri Lanka.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, the fish market-related cluster was linked to almost all the districts, followed by a highly intensified New Year-related outbreak in April that resulted in a substantial degree of community spread (5). The recent rapid surge of infective cases and deaths that occurred in August 2021 had dramatically crippled the health system due to the widespread delta (B.1.617.2) variant (5,6) across the country. However, the true extent of the disease among HCWs has been difficult to determine in Sri Lanka, yet PCR testing from nasopharyngeal swabs is challenging with limited resources.…”
Section: Introductionmentioning
confidence: 99%